Special Courts for the Settlement of Regional Head Election Disputes in the Context of Realizing the Principle of Legal Certainty and Orderly Governane - Abd. Rahmattullah Rorano S. Abubakar; Atma Suganda (Journal Research of Social Science, Economics, and Management, 2022)
Law Number 12 of 2008 violates the 1945 Constitution of the Republic of Indonesia. Article 157(1) of Law Number 8 of 2015 stipulates that the settlement of disputes over the results of direct regional head elections is under the jurisdiction of a special court, but until the establishment of a special court, the Constitutional Court still has the power to resolve disputes over the results of direct elections. The results of the research are expected to be able to answer constitutional issues in Indonesia, especially regarding the urgency of the establishment of a special court for the election of regional heads and the extent to which the design model for special courts for the election of regional heads is in order to ensure the quality of democracy. In addition, as a discourse for students who are in the field of Constitutional Law, it requires constructive thinking. This research uses a normative juridical approach which emphasizes literature research. The portrait of dispute resolution on the results of regional head elections continues to experience dynamics along with interpretations of the institutionalization of regional head elections as part of the general election regime or not.